Degradation and corrosion inhibitors for MEA-based CO2 capture plants. (July 2016) - Fytianos, Georgios; Vevelstad, Solrun J.; Knuutila, Hanna K.
Highlights: Non-toxic to humans degradation and corrosion inhibitors for MEA-based CO2 capture. Both oxidative and thermal degradation was studied. Optimal concentration of two of the inhibitors is investigated. Abstract: In amine based post-combustion CO2 capture and storage, solvent degradation and corrosion of steel materials are the main operational challenges. In this paper the focus was on minimizing degradation and corrosion by addition of inhibitors. The tested amine solution was 30 wt% of the benchmark solvent ethanolamine (MEA). The tested inhibitors were pyrogallol, alpha, alpha′-(1-methylethylenediimino)di- ortho -cresol, carbohydrazide, 2-butanone oxime (MEKO), tricine and 1, 3-diaminopropane- N, N, N′, N ′-tetraacetic acid (PDTA). The tests were performed under oxidative degradation conditions. After two weeks, PDTA showed the best inhibition performance. In addition to the oxidative degradation experiments, the thermal stability of carbohydrazide and PDTA were tested at 120 °C. After 2 weeks at stripper conditions, the PDTA loss was less than 50%. However, PDTA showed high metal concentration, indicating possible corrosion problems on the steel surface. Carbohydrazide, on the other hand, showed excellent corrosion protection properties, but it is not stable at 120 °C.